Siagonodon borrichianus (degerbøl’s blindsnake): Predation - Aragon y Traverso, Juan Héctor (2019)
Siagonodon borrichianus (Leptotyphlopidae) occurs in the southern Monte Desert and northwestern Patagonian regions of Argentina (Cei 1993. Reptiles del Centro, Centro Oeste y Sur de la Argentina. Herpetofauna de Zonas Áridas y Semiáridas. Monogr. IV Mus. Reg. Sci. Nat., Torino. 542 pp.; Fulvio-Pérez et al. 2010. Herpetol. Notes 3:65–67). Here we report a case of predation and the first record of S. borrichianus for Parque Provincial Ischigualasto, Departamento Valle Fértil, San Juan, Argentina (30.09779°S, 67.8336°W; SAD; 1331 m elev.). Two adult specimens of S. borrichianus were found in the fresh (<1 d old) regurgitate of a Pampas Fox (Lycalopex gymnocercus) along with two scorpions (Timogenes sp.), six cicadas (Cicadidae), bits of an unidentified lizard, numerous whole fruits/seeds of Chañar (Geoffroea decorticans), and blades of grass. Most of these food items had been chewed to varying degrees, but showed no obvious signs of chemical digestion, which facilitated their identification. Blindsnakes are infrequently encountered in nature because of their fossorial habits, but this species has also been reported in the diet other local vertebrates (e.g., toads; Quiroga et al. 2007. Herpetol. Rev. 38:208).